Barriers to Condom use among the Youth in a Municipal Town in Ghana - Abdul-Kabir, M.; Otupiri, Easmon; Opare, D. (Journal of the Ghana Science Association, 2023)
This is an article published in Journal of the Ghana Science Association Vol. 9 (2) 2007: pp. 76-84; DOI:10.4314/jgsa.v9i2.18016